The Implementation of Meunasah-based Sharia in Aceh: A Social Capital and Islamic Law Perspective - Nurdin, Abidin; Kasim, Fajri M.; Rizwan, Muhammad; Daud, Mahmuddin (Samarah: Jurnal Hukum Keluarga dan Hukum Islam, 2021)
This research examined meunasah as the social capital in implementing Islamic law in Aceh. It aimed to explain the social capital of meunasah concerning its role and functions in supporting the Islamic law implementation in Aceh. This research has its root in studying the sociology of law, emphasizing the empirical legal analysis within the society. The researchers used social capital, which consisted of cognitive and structural aspects as a theoretical framework, and interviews, literature study, and observation, as the data collection methods. This study found that meunasah had a central position in Acehnese society as a center for religious activities, a place to learn the Qur’an, social activities, and as a customary institution. Since time immemorial, meunasah has played a central role as a center for community activities at the gampong level. Even though meunasah had transformed itself into a mosque in urban areas, its function and role remained as a place for internalizing the Islamic law principles, as a medium for socializing Islamic law, and as a center for religious, social activities. This study argues that meunasah can still be the ‘glue’ of social networks with its religious, social, and customary values as a cognitive, social capital. On another side, imuem meunasah can be considered a structural social capital. Meunasah, as part of social institutions, can support social order and order, which is a social function of law. Without the support of meunasah as a cognitive social capital, the researchers argue that Islamic law will be difficult to be internalized in society.